Radioactivity monitoring in foodstuff and drinking water - An overview of performance of EU laboratories based on interlaboratory comparisons. (February 2017) - Sobiech-Matura, Katarzyna; Máté, Borbála; Altzitzoglou, Timotheos
Abstract: A compilation of the reported results of food and drinking water related interlaboratory comparisons conducted by the Joint Research Centre Institute for Reference Materials and Measurements is presented in this paper. An overview of analytical methods used by the participating laboratories, their overall performance as well as the evaluation of individual laboratories is assessed. The results show that the quality of input data into Radionuclide Environmental Monitoring database (REMdb) of the European Commission is acceptable but in some cases improvement is necessary. Harmonisation of the results obtained by different laboratories involved in REMdb and other European Union monitoring networks is worth the effort. Highlights: Results of 4 food and drinking water related interlaboratory comparisons analysed. Good performance of laboratories for 137 Cs and 40 K. Improvement needed for 226, 228 Ra and gross alpha/beta measurements in drinking water.